The Adoption and Implementation of High-Performance Work System in Subsidiaries of Japanese Multinational Companies in Vietnam: a Qualitative Study - Tran, Huy Phuong; Dinh, Thi Ngoc Quynh; Nguyen, The Kien (Organizacija, 2022)
: Managing human resource in foreign subsidiaries of Multinational Companies (MNCs) has been a challenging task due to the cultural diversity. High Performance Work System (HPWS) has been adopted by headquarters of MNCs in their subsidiaries as a form of control. The current research aims to explore the adoption and implementation of HPWS in subsidiaries of Japanese MNCs in Vietnam. : A qualitative research design was conducted with data collected from semi-structured in-depth interviews with 33 managers working in 11 subsidiaries of Japanese MNC in Vietnam. Content analysis was used to analyze the data. The results suggested that although HPWS was not fully implemented in these establishments, ability enhancing, motivation enhancing and opportunity enhancing bundle of HPWS were adopted to a varying extent. In addition, HPWS was adopted as a reactive response rather than a strategic choice. Finally, cost-benefit consideration may provide explanation for the non-systematic implementation of HPWS in affiliations of Japanese MNCs in Vietnam. The research provides some evidences to support the best-fit approach to HPWS adoption and implementation. Although HPWS has the potential to improve organizational performance, it must be internally aligned with the context of the organization.